Seventeen years of Kasai portoenterostomy for biliary atresia in a single Southeast Asian paediatric centre. (8th November 2016) - Chiang, Li Wei; Lee, Chuan Yaw; Krishnaswamy, Gita; Nah, Shireen Anne; Kader, Ajmal; Ong, Christina; Low, Yee; Phua, Kong Boo
Abstract : Aim: Biliary atresia (BA) has preponderance in Asian populations with Kasai portoenterostomy (KP) regarded as the first‐line standard of care. Yet reports from Southeast Asia remain scant. This study reviews the demographics, short‐ and medium‐term outcomes for our cohort, and evaluates prognostic factors for outcome. Methods: All patients diagnosed with BA between January 1997 and December 2013 were included. Clinical data were obtained from medical records. Jaundice clearance was defined as total bilirubin < 20 µmol/L within 6 months after KP. Two‐year and 5‐year native liver survival (NLS) were determined. Prognostic factors examined included gender, ethnicity, associated anomalies, age at KP, post‐KP cholangitis and clearance of jaundice within 6 months. Results: Of 58 patients studied, 31(53.4%) were male. Median age at time of KP was 53 days (range: 28–127). Ethnic distribution showed 32 (55.2%) Chinese, 16 (27.6%) Malays and 10 (17.2%) others. Twenty‐one (36.2%) patients achieved jaundice clearance by 6 months. Two‐year NLS rate was 36 out of 50 (72%), while 5‐year NLS rate was 16 out of 35 (45.7%). Only clearance of jaundice within 6 months had a significant association with NLS ( P = 0.006). All other factors showed no significant impact on outcome. Conclusions: Our short‐ and medium‐term outcomes after KP for BA are comparable with those reported by most international centres. However, prognostic factors such as age at KP, cholangitis episodes and associated anomalies did not show significant correlation; only clearance of jaundice within 6 months was significantly predictive of NLS.